PERANAN BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) KOTA PAYAKUMBUH TERHADAP SENGKETA KONSUMEN - Nedi Rinaldi (JCH (Jurnal Cendekia Hukum), 2019)
The Consumer Dispute Settlement Agency (BPSK) as a product of Law Number 8 of 1999 concerning Consumer Protection (UUPK) in conjunction with Decree of the Minister of Industry and Trade Number: 350/MPP/Kep/12/2001 concerning Implementation of Duties and Authorities of abbreviated Consumer Dispute Resolution Bodies BPSK and the Minister of Trade Regulation Number: 06/M-DAG/PER/2/2017, are institutions for resolving consumer disputes outside the court that should be part of efforts to protect consumers (end) categorized as weak when disputing with stronger business actors . The reality to date, BPSK still has many weaknesses and shortcomings. This condition is exacerbated by the growing strength of neoliberalism that affects the global economic system, which is realized or not has occurred in the strong economic control of business actors against the weak (consumers). This research is field research, namely field research with interview techniques to the parties involved that are directly related to the problem the author discussed, namely Payakumbuh City BPSK and aims to examine the efforts that can be done to optimize BPSK as an institution of consumer dispute resolution in outside the court that is fast, useful and meets the value of justice for the consumer community. This paper is based on a study of prime data and secondary data analyzed qualitatively. Based on the results of the study, efforts can be made to optimize Payakumbuh City BPSK which was formed in 2015 based on the Decree of the Minister of Trade of the Republic of Indonesia Number: 646 /M-DAG/Kep/4/2015, dated April 8, 2015 which can help consumers who feel disadvantaged by business actors.